THE IMPLEMENTATION OF METACOGNITIVE STRATEGIES IN SEMINARIANS’ ONLINE READING ACTIVITY - Sarce Lobi; Concilianus Laos Mbato (Magister Scientiae, 2024)
The article explores the role of metacognitive strategies in improving online reading performance among seminarians. With the rise of digital technology and the increasing reliance on online resources, it is crucial to equip seminarians with efficient metacognitive tools to enhance their understanding, analytical thinking, and overall educational journey. The study aims to identify specific metacognitive strategies that seminarians implement to improve their online reading skills. The study found that seminarians were aware of metacognitive strategies, with a high percentage using planning, monitoring, and evaluation strategies in reading. Regardless, metacognitive strategy instruction is widespread among seminaries and has been successfully implemented, providing an effective alternative for teaching reading comprehension skills at the senior high school level. The study suggests practical ways for students to build their self-regulated-learning skills particularly in reading.